Nanodust detection near 1 AU from spectral analysis of Cassini/Radio and Plasma Wave Science data. Issue 15 (7th August 2014) - Schippers, P.; Meyer‐Vernet, N.; Lecacheux, A.; Kurth, W. S.; Mitchell, D. G.; André, N.
Abstract Nanodust grains of a few nanometers in size are produced near the Sun by collisional breakup of larger grains and picked up by the magnetized solar wind. They have so far been detected at 1 AU by only the two STEREO spacecraft. Here we analyze the spectra measured by the radio and plasma wave instrument onboard Cassini during the cruise phase close to Earth orbit; they exhibit bursty signatures similar to those observed by the same instrument in association with nanodust stream impacts on Cassini near Jupiter. The observed wave level and spectral shape reveal impacts of nanoparticles at about 300 km/s, with an average flux compatible with that observed by the radio and plasma wave instrument onboard STEREO and with the interplanetary flux models.